In-line rheo-optical characterization in gram scale extrusion of materials - Teixeira, P. F. (2011)
Extruders are a fundamental part of any extrusion or compounding line. Single-screw extruders are of general-purpose application, while intermeshing twin-screw machines have found special application niches, mainly because of their good mixing capabilities. When only small quantities of (expensive or experimental) materials are available, it is often necessary to extrude at small, laboratorial scales. In addition, the in-situ characterization of material structure and viscoelastic properties is essential for understanding the interplay between process parameters and the final properties of the extrudate. The aim of this work is to couple a novel small scale modular single / twin-screw extrusion system, with well-controlled outputs in the range 30-300 g/h, to a slit die able to perform in-line rheo-optical characterization. The mini-extruder is equipped with ports that allow sample collection or non-intrusive analysis to be performed along its axis at desired locations. Rheometrical functions such as shear viscosity and normal-stress differences can be measured simultaneously with small angle light scattering patterns or optical microscopy imaging. Both rheological and optical validations of the equipment are presented and a preliminary study of a model polymer blend is reported. This new small scale rheo-optical tool opens the route to the study of complex materials at shear rates that cannot be achieved by state-of-the-art bench top rheometers. Alternatively, industrial polymer blends can be studied in real processing conditions.